Supplement with Cystoseira canariensis promotes an increase of resistance to the maximum load in the grastrocnemius muscle of female rats - Douglas Reis Abdalla; Eliana Silva Cassimiro Araújo; Leonardo César Carvalho; Dernival Bertoncello (Universidade de São Paulo, 2014)
Was evaluated the maximum load supported by the grastrocnemius muscle of female rats after the ministering of Cystoseira canariensis, either associated or not to swimming. Twenty-eight young Wistar female rats were used, divided into 4 groups: control (C, n=7); supplement (S, n=7); supplement and swimming (SSw, n=7); swimming (Sw, n=7). Each one pertaining to the groups S and SSw received 20 mg of myostatin inhibitor per day. The swimming consisted in an aerobe protocol, three times in a week, during eight weeks. The right grastrocnemius muscle of each animal was removed and a tension test was performed in an Emic testing machine. The results (Mean±SEM) were evaluated through ANOVA and Tukey test (p<0.05). A significant difference for maximum load (in N) was verified among the groups C (35.41±1.06) and S (39.98±1.15); Sw (27.94±2.19) and S (39.98±1.15); Sw (27.94±2.19) and SSw (37.78±1.28). In relation to the stretching at the maximum limit (in x10-3m) at the maximum load, the group SSw obtained a value (20.68±1.19) significantly greater than the groups C (17.15±1.11), S and Sw (16.11±1.60). There was a significant difference for body weight gain among the groups treated with supplement and supplement associated to the swimming, with smaller values for this last. The myostatin inhibitor either, associated or not to the swimming, promotes an increase of resistance to the maximum load in the tension test in grastrocnemius muscle of young female rats.